2018
DOI: 10.1002/ps.5106
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the efficacy of two insect detection methods with Riptortus pedestris (Hemiptera: Alydidae): portable harmonic radar system and fluorescent marking system

Abstract: The portable harmonic radar system can be an effective detection method in either landscape during both day and night. Furthermore, the fluorescent marking system can be a reliable tool at night as well. Lastly, combining both methods can improve the night detection. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 55 publications
(179 reference statements)
0
20
0
Order By: Relevance
“…(Acari: Ixodidae), (D) nymph of H. longicornis , and (E) adult of H. longicornis . Previous studies demonstrated that R. pedestris and H. halys were successfully applied with the fluorescent marking system tested in this study …”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…(Acari: Ixodidae), (D) nymph of H. longicornis , and (E) adult of H. longicornis . Previous studies demonstrated that R. pedestris and H. halys were successfully applied with the fluorescent marking system tested in this study …”
Section: Introductionmentioning
confidence: 78%
“…However, such information is largely unknown rooting from technical barriers that prevent reliable tracking of the movement of small organisms in the field. Recently, Rice et al have demonstrated that fluorescent marking shows improved efficacy in detection of H. halys when it is paired with a handheld UV laser, and Kho et al have shown the applicability of an enhanced FMS in the detection of R. pedestris . Therefore, the present study aimed to evaluate the application potential of the FMS for different life stages of H. longicornis and measure the detectability of marked individuals illuminated by UV lasers …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations